The Plans for Russian Expansion in the New World and the North Pacific in the Eighteenth and Nineteenth Centuries - Andrei V. Grinev (European Journal of American Studies)
The theme of Russian expansion in the New World and North Pacific in the eighteenth to mid-nineteenth centuries has repeatedly attracted the attention of Russian and foreign scholars. At the same time, the topic evokes discussion in scholarly historiography as authors frequently adhere to diametrically opposing points of view. In this paper we will investigate the elaboration of plans for Russian territorial expansion in the New World, noting that these plans often were an organic part of larger plans to include the whole North Pacific among the possessions of the Russian Empire.